MRI‐assessed locus coeruleus integrity is heritable and associated with multiple cognitive domains, mild cognitive impairment, and daytime dysfunction. Issue 6 (13th February 2021) - Elman, Jeremy A.; Puckett, Olivia K.; Beck, Asad; Fennema‐Notestine, Christine; Cross, Latonya K.; Dale, Anders M.; Eglit, Graham M. L.; Eyler, Lisa T.; Gillespie, Nathan A.; Granholm, Eric L.; Gustavson, Daniel E.; Hagler, Donald J.; et al.
Abstract: Introduction: The locus coeruleus (LC) undergoes extensive neurodegeneration in early Alzheimer's disease (AD). The LC is implicated in regulating the sleep–wake cycle, modulating cognitive function, and AD progression. Methods: Participants were 481 men (ages 62 to 71.7) from the Vietnam Era Twin Study of Aging. LC structural integrity was indexed by neuromelanin‐sensitive magnetic resonance imaging (MRI) contrast‐to‐noise ratio (LCCNR ). We examined LCCNR, cognition, amnestic mild cognitive impairment (aMCI), and daytime dysfunction. Results: Heritability of LCCNR was .48. Participants with aMCI showed greater daytime dysfunction. Lower LCCNR was associated with poorer episodic memory, general verbal fluency, semantic fluency, and processing speed, as well as increased odds of aMCI and greater daytime dysfunction. Discussion: Reduced LC integrity is associated with widespread differences across cognitive domains, daytime sleep‐related dysfunction, and risk for aMCI. These findings in late‐middle‐aged adults highlight the potential of MRI‐based measures of LC integrity in early identification of AD risk.